A comparative view of patients’ rights in UK and Malaysia - Md Noor Alam, Hazlina Shaik (Opción, 2019)
Who shall be the ones to ultimately decide who deserves treatment? Thus, the most significant question that now begs to be answered is, by the medical profession more often than not, who exactly do we treat? In trying to reach the elusive goal of seemingly perfect health, a comparative study of the UK and Malaysian health care system has becomes inevitable. The results showed that patients‟ rights, as well as the relationship between medical accountability and ethics, and will further elaborate on the developments of the two concepts in Malaysia.